Damage assessment of RC bridge piers under rockfall impact and evaluation of a steel-sand protective structure. (January 2023) - Zhong, Hanqing; Hao, Chaoran; Yu, Zhixiang; Lyu, Liang; Wu, Anjie
Abstract: The damage and collapse of the reinforced concrete (RC) piers subjected to rockfall impact occur frequently in mountainous areas. In the present scrutiny, a full-scale numerical model of a bridge pier is established to examine the mechanical behaviors of RC piers against rockfall, which is planned to be explored in three aspects: residual strength analysis, structural damage evaluation, and protection measures. The dynain file method is introduced to reach the realization of the stress initialization of the impacted pier. The RC pier model and the dynain file method, constructed and realized through the software LS-DYNA respectively, are illustrated in detail as well as their validations. The complicated collision process between the rockfall and the RC pier is first interpreted. Subsequently, the study on the pier residual axial capacity is carried out based on the dynain file approach. Further, a calculation model for the residual axial capacity of the impacted pier is proposed by considering the rock mass, velocity, concrete strength, and pier diameter. The influential parameters on the maximum impact force and residual axial capacity of the impacted pier are also displayed and discussed. Furthermore, the damage index of the bridge pier under the rockfall impact is established based on the residual axial capacity, and the pier's impact-damage degree is analyzed through the isodamage curves. Finally, a steel-sand composite structure is introduced to protect the RC pier from rockfall impact. The obtained results demonstrate that the dynain file method can be suitably applied in the residual axial capacity analysis of RC piers subjected to rockfall. The proposed calculation formula can be appropriately adopted to evaluate the post-impact residual axial capacity of RC piers. The detailed parameter analysis indicates that the pier diameter has a remarkably influential effect on the rockfall impact force and the pier's residual axial capacity. Additionally, the composite protective structure can enhance anti-collision performances.